Current management of pregnancy-related low back pain: a national cross-sectional survey of UK physiotherapists. Issue 1 (March 2016) - Bishop, A.; Holden, M.A.; Ogollah, R.O.; Foster, N.E.
Abstract: Background: Pregnancy-related low back pain (LBP) is very common. Evidence from a systematic review supports the use of exercise and acupuncture, although little is known about the care received by women with pregnancy-related back pain in the UK. Objective: To describe current acupuncture and standard care management of pregnancy-related LBP by UK physiotherapists. Design: Cross-sectional survey of physiotherapists with experience of treating women with pregnancy-related LBP from three professional networks of the Chartered Society of Physiotherapy. Methods: In total, 1093 physiotherapists were mailed a questionnaire. The questionnaire captured respondents' demographic and practice setting information, and experience of managing women with pregnancy-related back pain, and investigated the reported management of pregnancy-related LBP using a patient case vignette of a specific, 'typical' case. Results: The overall response rate was 58% (629/1093). Four hundred and ninety-nine physiotherapists had experience of treating women with pregnancy-related LBP and were included in the analysis. Most respondents worked wholly or partly in the UK National Health Service (78%). Most respondents reported that they treat patients with pregnancy-related LBP in three to four one-to-one treatment sessions over 3 to 6 weeks. The results show that a range of management strategies are employed for pregnancy-related LBP, and multimodal management is common. The most common reported treatment was home exercises (94%), and 24% of physiotherapists reported that they would use acupuncture with the patient described in the vignette. Conclusions: This study provides the first robust data on the management of pregnancy-related LBP by UK physiotherapists. Multimodal management is common, although exercise is the most frequently used treatment for pregnancy-related LBP. Acupuncture is used less often for this patient group.